Neonatal and pediatric terminal patients with congenital malformations of the circulatory system: lethality survey in Brazil and integrative review of palliative care in the ICU (Research, Society and Development, 2023)
Palliative care instigates the bioethical and technical discussion of intensive care in pediatric cardiology. The aim of the study was to outline an overview of neonatal and pediatric patients with congenital malformations of the circulatory system, evaluating mortality indicators in Brazil and palliative care in the ICU. An epidemiological study using the Datasus database raised the general hospital mortality rate or due to congenital malformations of the circulatory system in the age group of less than 1 year or between 1 and 4 years. An integrative review using the PubMed database retrieved original thematic publications between 2017 and 2022, adopting the methodological approach of PRISMA and JBI and evidence level 1B from Oxford or high from GRADE. Despite the decennial decline in hospital lethality rates due to congenital malformations of the circulatory system, the 1-year age group persists as more critical care than the 1- to 4-year age group, revealing regional asymmetries in the national context. Randomized multicenter studies on hypoplastic left heart syndrome in children with stage 1 to 2 palliation were more frequent, with great heterogeneity of interventions and clinical results applied to pediatric cardiology. The lack of experiences with critical neonates and family-centered palliative care call for future studies.